The influence of storage method on the transparency of pig crystalline lens - Artigas,Cristina (2019)
ABSTRACT Purpose: The porcine eye is frequently used as a research model. This paper analyzes the effect of different storage methods on the transparency of pig crystalline lens. Methods: A spectral transmission curve (from 220 to 780 nm) for the crystalline lens was determined experimentally after storage in different conditions: saline solution, formalin, castor oil, and freezing at -80°C. The total transmission in the visible spectrum, which was used as an index of transparency, was calculated from these curves. For comparative purposes, fresh lenses were evaluated and used as controls. Results: Storing the porcine crystalline lens in saline solution or castor oil resulted in a transparency loss of approximately 10% after 24 h and storage in formalin resulted in a loss of nearly 30%. Storage by freezing at -80°C for 4 weeks maintained the transparency of the crystalline lens; the spectral transmission measured immediately after defrosting at room temperature coincided exactly with that of the freshly extracted lens. Conclusions: The transparency of porcine crystalline lens is affected by the storage method. The visible spectrum is the most affected, evidenced by the effect on the transparency and consequently the amount of light transmitted. The results show that freezing at -80°C maintains the transpa rency of the crystalline lens for at least 4 weeks.